Effect of two milk supplements and two ways of administration on growth performance, welfare and fecal microbial ecology of suckling piglets - Correa, Federico; Luise, Diana; Negrini, Clara; Ruggeri, Roberta; Bosi, Paolo; Trevisi, Paolo (Frontiers in Veterinary Science, 2023)
Introduction The aim of this study was to evaluate the effect of two MS formulas, DanMilk™ (AB Neo, Denmark) (MS1) and Neopigg® RescueMilk (Provimi, Netherlands) (MS2) administered manually and to compare two ways of administration (manual vs automatic) of MS1 on growth performance, health, fecal microbial profile, behavior, and skin lesions of piglets during suckling and post-weaning. Methods Forty litters (528 piglets) were divided into 4 groups: 1) Control group receiving no MS (CON); 2) MS1 administered automatically (A-MS1); 3) MS1 administered manually (Ma-MS1) 4) MS2 administered manually (Ma-MS2). All groups had access to sow milk and creep feed. On day 5 after birth (d0), litters were equalized (13.2 piglets/litter ± 0.8 SD), thereafter no cross-fostering was allowed. Piglets were weighed at day 5 after birth (d0), at the end of milk supplementation (d14), at weaning (d21 of the trial, 26 days of age) and ten days post-weaning (d31). Piglet welfare was assessed using behavioral and lesion measures at d4 and d10. Feces were collected at d14 and d21. Results and discussion During the suckling period, A-MS1 had lowest mortality (p < 0.05), while Ma-MS1 had lower mortality compared with CON and Ma-MS2 (p < 0.05). Negative social behavior at d4, was more frequent in MS groups (A-MS1, Ma-MS1, Ma-MS2) compared to CON group (p = 0.03). Growth performance and lesion prevalence were not affected by MS provision. During lactation, Ma-MS2 group had a higher percentage of piglets not eating during suckling at d18 compared with Ma-MS1 (p = 0.03). MS1 increased microbial diversity compared with CON at d14 (Chao1, p = 0.02; Shannon, p = 0.03) and compared with CON (Shannon, p < 0.05; InvSimpson, p = 0.01) and Ma-MS2 (Chao1, p < 0.05; Shannon, p = 0.05, InvSimpson p = 0.01) at d21. Groups that received MS1 were characterized by genera producing short-chain fatty acids (SCFAs), i.e., Lachnospiraceae (A-MS1) and Oscillospiraceae (Ma-MS1). MS composition and availability can contribute to reduce piglet's mortality during the suckling phase and can also affect intestinal microbiota by favoring the presence of SCFAs producing bacteria.